Dual Photoredox and Nickel Catalysed Reductive Coupling of Alkynes and Aldehydes. Issue 19 (18th July 2022) - Calogero, Francesco; Magagnano, Giandomenico; Potenti, Simone; Gualandi, Andrea; Fermi, Andrea; Ceroni, Paola; Giorgio Cozzi, Pier
Abstract: A regioselective vinylation of aromatic and aliphatic aldehydes promoted by the merging of photoredox and nickel catalysis is here reported. A comprehensive investigation on the reaction conditions allowed the disclosure of a valid and reproducible protocol based on a nickel‐mediated reductive coupling approach under visible light irradiation. The employment of 3CzClIPN (2, 4, 6‐tris(carbazol‐9‐yl)‐5‐chloro‐isophthalonitrile) as the photocatalyst and Hantzsch's ester as the sacrificial organic reductant replace the use of boron‐, silicon‐ or zinc‐based reducing agents, making this method a worthy alternative to the already known protocols. The developed mild reaction conditions allow the access to a wide range of substituents decorating both the aldehyde and the alkyne. Moreover, careful photophysical investigations shed light on the mechanism of the reaction. Abstract :